City on fire : a novel - Winslow, Don, 1953- (William Morrow, 2022)
Two criminal empires together control all of New England. Until a beautiful modern-day Helen of Troy comes between the Irish and the Italians, launching a war that will see them kill each other, destroy an alliance, and set a city on fire. Danny Ryan yearns for a more "legit" life and a place in the sun. But as the bloody conflict stacks body on body and brother turns against brother, Danny has to rise above himself. To save the friends he loves like family and the family he has sworn to protect, he becomes a leader, a ruthless strategist, and a master of a treacherous game in which the winners live and the losers die. From the gritty streets of Providence to the glittering screens of Hollywood to the golden casinos of Las Vegas, Danny Ryan will forge a dynasty.